2017
DOI: 10.15359/ru.31-1.8
|View full text |Cite
|
Sign up to set email alerts
|

Selección de hábitat de Lontra longicaudis (Carnivora, Mustelidae) bajo la influencia de la represa hidroeléctrica del río Peñas Blancas y sus tributarios, Alajuela, Costa Rica

Abstract: Los cambios producidos por actividades humanas sobre los ecosistemas acuáticos reducen y reconfiguran los hábitats disponibles. Por ello, el objetivo de este estudio fue evaluar la selección de hábitat de la nutria neotropical (Lontra longicaudis), en zonas con influencia de la represa hidroeléctrica del río Peñas Blancas y algunos de sus tributarios, con el fin de recomendar acciones para la conservación de la nutria. Se muestreó el río Peñas Blancas y tres de sus tributarios en busca de indicios de la nutria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…In northeastern Costa Rica, it has been suggested that otters use larger, less urbanized rivers, while at the local-scale selecting for areas with higher tree density [4]. This finding was similar to central Costa Rica, where occupancy was found to increase with forest cover and river width at the local-scale [6].…”
Section: Introductionmentioning
confidence: 62%
See 3 more Smart Citations
“…In northeastern Costa Rica, it has been suggested that otters use larger, less urbanized rivers, while at the local-scale selecting for areas with higher tree density [4]. This finding was similar to central Costa Rica, where occupancy was found to increase with forest cover and river width at the local-scale [6].…”
Section: Introductionmentioning
confidence: 62%
“…The majority of research to date has been carried out in Brazil and Mexico, with a lack of information from Central America [2]. Thus, there remains a lack of basic ecological information such as diet and habitat use in this region [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research into the impacts of river infrastructure on Costa Rica is related to other topics, such as mammals (Picado, Parallada, Mora, & Sánchez, 2017), plants (Benavides, Barboza, Rodríguez, & Gairaud, 2015;Campos, 2017) and habitat fragmentation (Farah, 2016). The results of this study into the morphology and ecology of a fish species in relation to the burst speed can serve as a baseline of information for the country.…”
mentioning
confidence: 99%